Kuasa Tuhan Nyata Sempurna dalam Kelemahan Manusia di Tinjau dari II Korintus 12:9 - Eka Preskila (Sekolah Tinggi Theologia Nazarene Indonesia, 2019)
In II Corinthians, Paul wrote if he has a thorn in the flesh, and he asked the Lord about that, that it depart from him. As we know Paul was a great missionary, how his obedience and braveness for Christ, he is one of the famous Prophetes. But God’s said to Paul if His Grace is enough for him, and His power’s made perfect in weaknes. So, what the meaning of the thorn? What God’s answered to Paul about that? And actually, what Paul felt after God’s answered?